Automated infrastructure: COVID-19 and the shifting geographies of supply chain capitalism. (April 2022) - Lin, Weiqiang
In recent years, geographers have evinced how infrastructure constitutes the bedrock of supply chain capitalism and its oppressions. This article interrogates how advanced automation – comprising robotics, artificial intelligence and software – is poised to politicize this infrastructural space further on the heels of the COVID-19 pandemic. Reflecting on COVID-19 developments, the article shows how logistics is turning to advanced automation to drive productivity outside labour, spur self-service consumption through digital technologies and contest labour's future. As automated infrastructure threatens to take hold, a configuration of exchange that increasingly places labour, but not profits, outside of capital's circulations will need to be challenged